Predicting intentions to text and call while driving using the theory of planned behaviour. (October 2018) - Sullman, M.J.M.; Hill, T.; Stephens, A.N.
Highlights: The present study was conducted in Ukraine. Our study examined intentions to use mobile phones while driving using the Theory of Planned Behaviour (TPB). A positive attitude towards using mobile phones was the key predictor of intentions. Perceived behavioural control was positively associated with mobile phone use. A few associations were found between subjective norms and mobile phone use. Abstract: There is extensive evidence that using a mobile phone while driving causes degradation in driving performance, and thereby results in reduced safety on the road. The present study examined intentions to use mobile phones while driving using the Theory of Planned Behaviour (TPB). A total of 212 Ukrainian drivers (mean age = 35 years SD  = 10 years; males = 82%) completed a survey that included measures of the TPB components related to intentions to send or read text messages or to make or receive handheld phone calls across two different scenarios; one where they were running late, and the other when they were not in a hurry. Measures of the frequency of mobile phone use were also collected. The results showed that 63% of the sample reported using a mobile phone while driving at least daily, with the most frequent types of usage being making and answering a phone call with a handheld device. The most consistent predictor of intentions to interact with a mobile phone while driving was having a positive attitude towards doing so. Perceived behavioural control was also significantly and positively associated with mobile phone use while driving, but only a small number of associations were found with subjective norms. Our results suggest that intentions to interact with mobile phones while driving may be context specific.